Combined procedures for surgical short bowel syndrome: experience from two European centres. Issue 4 (13th December 2022) - Gigola, Francesca; Coletta, Riccardo; Certini, Martina; Del Riccio, Marco; Forsythe, Lynette; Morabito, Antonino
Abstract: Background: Autologous gastrointestinal reconstructive surgery (AGIR) has become a key component of intestinal rehabilitation programs. However, the best surgical option for short bowel syndrome (SBS) remains unknown. This paper presents our experience using combined procedures as primary treatment. Methods: We collected data on SBS patients who underwent surgery from 2008 to 2021 in two tertiary European Centres. Combined procedures were defined as more than one technique used on the same patient. Charts were reviewed for demographics, type of procedures, complications, and outcomes. Data are presented as median and IQR. Wilcoxon signed rank was used for all paired analyses. Results: Twenty‐one children (12 females) underwent combined procedures. Preoperative median small bowel length was 20 cm (IQR: 15–35 cm); after lengthening, it was 35.5 cm (IQR: 30.75–50.50 cm) ( P < 0.001). Combined procedures were simultaneous in 15 patients and sequential in 6. At a median of 9.2 years (IQR: 7.55–9.78 years) follow‐up, complications were three bowel obstructions after strictures of anastomosis and two wound infections. Two patients achieved enteral autonomy, and others followed a weaning home parenteral nutrition regimen with a median of 4 nights off (IQR: 3–4 nights) starting with a median of 7 nights (IQR: 7–7 nights). Conclusions: Combined AGIR techniques are practical and safe in SBS treatment when tailored to meet patients' needs, combining lengthening, tailoring, and reducing transit time procedures. Therefore, combined AGIR may be considered a resource in intestinal rehabilitation units' armamentarium. Abstract : Autologous gastrointestinal reconstructive surgery has become a key component of intestinal rehabilitation programs for Short Bowel Syndrome. The best surgical option remains unknown, and some patients might benefit from more than one technique: we present our experience using combined procedures as primary treatment.